PHAryngeal electrical STimulation for early decannulation in TRACheotomised stroke patients with neurogenic dysphagia (PHAST-TRAC): a prospective randomised single-blinded trial - Dziewas, Rainer; Stellato, Rebecca; Van Der Tweel, Ingeborg; Walther, Ernst; Werner, Cornelius J.; Braun, Tobias; Citerio, Giuseppe; Jandl, Mitja; Friedrichs, Michael; Nötzel, Katja; Vosko, Milan R.; Mistry, Satish; et al. (Elsevier, 2018)
Background